Impacto das visitas domiciliares na asma grave pediátrica - Daniela Soares Rosa Ferreira (2017)
Objectives: To evaluate the effectiveness of home visits (HV) relating to the treatment of a group of children and adolescents with severe asthma. The evaluation took into consideration controlled home environment variables, drug adherence rates and inhalation technique scores. Methodology: A prospective interventional study was developed over a period of 12 months, in which 34 children and adolescents, aged between 3 and 17 years, were referred to the Multidisciplinary Centre for Patients with Asthma that is Difficult to Control (CEMAD). This Centre is linked to the pediatric pulmonology group at the Hospital das Clínicas (HC) which is a part of the Federal University of Minas Gerais (UFMG). A controlled, randomized study was conducted in which one group (of the afore mentioned subject group) received a home visit with a nurse and the other group received the same guidance but from the CEMAD team in in the outpatient unit at the hospital. The differences found between the groups and the outcomes were analyzed by reviewing the controlled home environment variables, inhalation technique (IT) scores, and the treatment adherence rate. Results: In the intervention group there was a statistically significant increase in the IT scores (p <0.05) and even after the elimination of critical errors from the first to the second evaluation, these results were maintained in the third evaluation. There were no significant changes in the IT scores of the controlled group. Throughout this period there were no significant changes in the controlled home environment variables or in the adherence rates to drug treatment in any of the groups. Conclusion: The results demonstrated that home visits was effective in improving inhalation technique scores in patients with severe asthma and in selected patients, it could be implemented.